2007
DOI: 10.1021/ja0722574
|View full text |Cite
|
Sign up to set email alerts
|

Orientational and Dynamical Heterogeneity of Rhodamine 6G Terminally Attached to a DNA Helix Revealed by NMR and Single-Molecule Fluorescence Spectroscopy

Abstract: Abstract:The comparison of Fö rster resonance energy transfer (FRET) efficiencies between two fluorophores covalently attached to a single protein or DNA molecule is an elegant approach for deducing information about their structural and dynamical heterogeneity. For a more detailed structural interpretation of single-molecule FRET assays, information about the positions as well as the dynamics of the dye labels attached to the biomolecule is important. In this work, Rhodamine 6G (2-[3′-(ethylamino)-6′-(ethylim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 46 publications
(71 reference statements)
3
48
0
Order By: Relevance
“…Cyanine dyes were found to stack frequently on the end of the DNA helix [62][63][64] and also rhodamines, terminally attached to a DNA duplex, show a dynamic equilibrium between various structural states. [61,65] Vaiana et al were among the first to perform MD studies on fluorophore/quencher pairs that were known to show efficient PET-quenching upon molecular contact. [12] They developed molecular force field parameters for the oxazine dye MR121 and the rhodamine dye R6G.…”
Section: Mr121 [E]mentioning
confidence: 99%
“…Cyanine dyes were found to stack frequently on the end of the DNA helix [62][63][64] and also rhodamines, terminally attached to a DNA duplex, show a dynamic equilibrium between various structural states. [61,65] Vaiana et al were among the first to perform MD studies on fluorophore/quencher pairs that were known to show efficient PET-quenching upon molecular contact. [12] They developed molecular force field parameters for the oxazine dye MR121 and the rhodamine dye R6G.…”
Section: Mr121 [E]mentioning
confidence: 99%
“…Although a rich and fascinating topic, its discussion would distract us from our main topic. We refer the interested reader to a recent introductory discussion in the context of detector development [14] as well as specialized and review articles [29][30][31][32][33][34][35][36][37][38][39][40][41]. We will briefly return to smFRET in Section VII, when discussing experimental results with SPAD arrays.…”
Section: Solution-based Single-molecule Fluorescence Spectroscopymentioning
confidence: 99%
“…This observation fits nicely to recent studies on the conformations of rhodamine 6G terminally attached to double-stranded DNA. [57] Additionally, we found that the rates of fluorescence fluctuations of donor emission observed after acceptor bleaching depend on the donor-acceptor distance. The duration of the probe in the fluorescent state increased with donor-acceptor separations and was at its longest on constructs where no acceptor was present.…”
Section: Increasing Probe Complexitymentioning
confidence: 81%
“…The observed fluctuations are then explained by structural fluctuations (bubble formation) in the DNA. [57] Our current interpretation is that a cationic guanosine radical is produced after ET occurs between ATTO 520 and the guanosine residue (DG 0 = 0.07 eV). This radical cation is then reduced by Cy5 through the p-stack of the DNA (DG 0 = À0.71 eV).…”
Section: Increasing Probe Complexitymentioning
confidence: 93%